BUDAYA PÈLÈT KANDUNG PERSPEKTIF ‘URF : (Studi Kasus di Desa Bunten Barat Kecamatan Ketapang Kabupaten Sampang) - Mahrus Soleh; Fahmi Assulthoni; Kamali Kamali (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
The culture of pellets is no longer strange to hear, especially in the Madurese community. In fact, this culture seems to be an obligation in every household when the wife is 7 months pregnant. As time goes by, the Pellet Kandung culture is no longer beautiful, there are many harsh comments from several figures, so that the Pellet Kandung culture is considered as if it is contrary to Islamic law and the concept of 'Urf. This research has benefits for theoretical use and practical use and this research uses a qualitative approach with a case study type of research, the presence of researchers in the field is one of the steps that will be taken by researchers as researchers and data collectors, the data sources in this research consist of data sources primary and secondary, data collection techniques used were observation, interviews and documentation. This research produces conclusions namely: a. In its implementation, Pèlèt Kandung begins with reading the letters of the Koran such as Surah Maryam and Surah Yusuf and also the prayer. This ritual is carried out after duhur or after Isha on the night of the full moon. In the implementation of the Pèlèt Womb the Dukun plays an important role in guiding the event procession. b. In reviewing the concept of 'Urf, the Pèlèt Kandung culture in West Bunten Village, Ketapang, Sampang includes 'Urf fi'li, 'Urf Sohihah and 'Urf Khas.